PENGALAMAN WANITA HAMIL LAMAHOLOT SEBELUM MASUK RUMAH SAKIT - Merry Kewa Solot (Citra Bangsa University - Literacy and Publishing Center (CBU-LPC), 2018)
Background: Maternal death is one of the important indicators to measure the health status of a country. The higher the Maternal Mortality Rate (MMR) the worse the health status of the country. Maternal Mortality Rate (MMR) in Indonesia is still high 289 / 100,000 Birth of Life (KH). In East Nusa Tenggara, (AKI) reached 133 / 100,000 KH, 3 of whom died at Dr.Hendrikus fernandez Larantuka Hospital. This death is caused by late admission to the hospital. Objective: To reveal the experience of pregnant women Lamaholot performed the pregnancy ritual ho'ing temodok before entering the hospital. Method: Using qualitative research design with phenomenology approach. Informants in this study were Lamaholot pregnant women who experienced complications of pregnancy and labor that were late to the hospital were 6 (six) people, the selection of informants was determined using purposive sampling. Data collection was done by indepth interview using semi-structured interview guidance. Data analysis using Interpretive Phenomenological Analysis (IPA). Results: Lamaholot pregnant women performing ho'ing temodok pregnancy ritual after getting the signs of labor, before doing the pregnancy ritual ho'ing temodok first prepare all the need for ritual, preparation and implementation of ho'ing temodok ritual takes a long time. Ritual pregnancy ho'ing temodok is a tradition of ancestral heritage that is rooted and must be done for the safety of mother and baby. Conclusion: Cultural factors play an important role in strengthening the beliefs of Lamaholot pregnant women. Understanding of pregnant women Lamaholot performs ho'ing temodok ritual after getting the signs of labor influenced by deep-rooted traditions and cultures. Although the preparation and implementation of the ho'ing pregnancy ritual temodok takes a long time but Lamaholot pregnant women are willing to do all the preparation and execution of the ritual. Keywords: Pregnant mother, ritual, hoing temodok, Lamaholot